2010
DOI: 10.1037/a0017297
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the strategies used by rats to solve a navigation task.

Abstract: Rats were trained in a triangular-shaped pool to find a hidden platform, whose location was defined in terms of two sources of information, a landmark outside the pool and a particular corner of the pool. Subsequent test trials without the platform pitted these two sources of information against one another. This test revealed a clear sex difference. Females spent more time in an area of the pool that corresponded to the landmark, whereas males spent more time in the distinctive corner of the pool even though … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(90 citation statements)
references
References 29 publications
6
81
2
1
Order By: Relevance
“…From this small set of findings, it appears that men might be better at using geometric cues compared to women. This would parallel the sex differences that have been found for rats in water-maze search tasks, where both sexes can use geometric or proximal feature cues to locate a hidden platform, but male rats rely more heavily on geometric cues and female rats prefer to use a proximal feature cue (Rodriguez, Chamizo, & Mackintosh, 2011;Rodriguez, Torres, Mackintosh & Chamizo, 2010). However, these studies were not about orientation, and therefore any claims about sex differences in reorientation ability are currently far from definitive.…”
Section: Section Summarymentioning
confidence: 79%
See 1 more Smart Citation
“…From this small set of findings, it appears that men might be better at using geometric cues compared to women. This would parallel the sex differences that have been found for rats in water-maze search tasks, where both sexes can use geometric or proximal feature cues to locate a hidden platform, but male rats rely more heavily on geometric cues and female rats prefer to use a proximal feature cue (Rodriguez, Chamizo, & Mackintosh, 2011;Rodriguez, Torres, Mackintosh & Chamizo, 2010). However, these studies were not about orientation, and therefore any claims about sex differences in reorientation ability are currently far from definitive.…”
Section: Section Summarymentioning
confidence: 79%
“…More important, it represents a challenge to any viable comprehensive theory, which must be able to account in precise quantitative terms for the pattern of effects, and make novel predictions. An interesting direction for future research has been indicated by recent studies on rodents which suggest that cue interaction (blocking, overshadowing, and facilitation) between geometry and features might be modulated by sex because male and female rats tend to assign different weights to these cues (Rodriguez, Chamizo, & Mackintosh, 2011;Rodriguez, Torres, Mackintosh, & Chamizo, 2010); this should be explored in additional species.…”
Section: Facilitation and Interference Effectsmentioning
confidence: 99%
“…In males, geometry overshadowed landmark learning, but landmark learning did not overshadow learning about geometry, while in females, landmark learning overshadowed learning about geometry, but geometry learning did not overshadow landmark learning. It was the more discriminable, salient, or preferred source of information (geometry for males and landmark for females, as shown by Rodríguez et al, 2010) that overshadowed the less discriminable, salient, or preferred cue.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hayward et al, who assessed salience on the basis of the performance of groups trained with each cue in isolation, found no evidence to support this. It remains to be seen whether the measure of salience employed by Rodríguez et al (2010)-namely, opposing the two cues and seeing which one wins-would have given the same result. An even more puzzling finding, from our point of view, is that McGregor et al (2009) found not only that landmarks did not overshadow geometry, but also that geometry failed to overshadow landmarks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation